Sistem, Mekanisme dan Permasalahan Pemeriksaan Keuangan di Indonesia - Muhammad Syahratul Ikhsan; M. Khairun Najmi Ali; Ratih Kusumastuti (Universitas 45 Surabaya, 2023)
The Supreme Audit Agency (BPK) is a government organization responsible for examining how the government spends its money. BPK is headquartered in the national capital and has representatives in every province. The responsibilities of BPK's audits include financial audits, performance audits, and audits with specific objectives. Financial audits cover the state's revenue and expenditure, as well as regional revenue and expenditure. The high level of corruption in Indonesia has led to some individuals becoming wealthy while others struggle. The causes of corruption also include the misuse of government funds by both the central and regional governments. BPK is responsible for ensuring that public institutions are run ethically and effectively. It oversees corruption by investigating and taking action against those responsible